Taking the fear out of apocalyptic preaching - Bashaw, Jennifer Garcia (2018)
In the last century of the American Church, fear has characterized much of apocalyptic preaching. Fear of apocalyptic texts has inhibited the preaching of them in some pulpits; fear of the future and fear of others has dominated the apocalyptic message in others. This article answers the question, How did apocalyptic preaching get so out of hand and what can we do to fix it? by providing a brief overview of apocalyptic preaching in America and by offering interpretive strategies and homiletical suggestions for preaching apocalyptic texts responsibly and without fear.
Keywords: Mark 13; Apocalyptic; Fear; Homiletics; Preaching